Response potato varieties (Solanum tuberosum L) to fertilizer application to organic chemistry and fertilization - Luna Murillo, Ricardo (2016)
Fertilization or fertilization of this crop is a major driving factor, aimed at obtaining proper nutrition as a basis to achieve the highest commercial yields per unit area. The aim of this study was to evaluate the agronomic response of two varieties of potato to the application of organic manure and chemical fertilizers. The application of organic fertilizers was performed at 0 and 60 days; manure (2.50 t ha-1), cattle manure (10 t ha-1) and vermicompost (0.70 t ha-1); 10-30-10 and 15-15-15 fertilizer (N, P and K, in percentage) at 0.38 t ha-1 each; at 0, 60 and 90 days, exposed on a design randomized complete block in factorial 2x3x2 + two witnesses and three repetitions. The research was conducted at the Hacienda San Isidro parish Mulaló, Cotopaxi province, and plant height, diameter tubers, quantity and weight of tubers per plant, yield per plot was measured. The results showed similar behavior in all treatments studied. It is concluded that the potato is a crop that responds favorably to the application of organic fertilizers or organic fertilizers and chemical fertilizers interaction, is a good option to reduce the use of chemical fertilizers.